An application of panel ARDL model with cointegration for portfolio management. (22nd March 2022) - Ilyas, Umer; Butt, Matti Ullah; Gulzar, Muhammad
The aims of this study are to explore the impact of macroeconomic variables on stock performance and to provide a knowledge platform with international applicability with the application of panel ARDL model with cointegration on Pakistan Stock Exchange (PSX) not only to have better development of portfolio but to overcome the deficiencies of conventional index base studies as well by finding this impact on not only every sector of PSX but upon each individual firm of the sector as well. For this purpose, monthly data for first quarter of 2005 until first quarter of 2020 was employed for exports, foreign direct investment, foreign exchange reserves, interest rate and inflation as independent variables and monthly stock prices as dependent variable. The results indicate that impact and response was significantly different for overall sector as compared to firms from within same sector for change in independent variables. This opens a new dimension of knowledge for portfolio managers.